Effects of different clones and inducing time on agarwood quality in grafted Qi-Nan Aquilaria sinensis (Lour.) spreng - Ming Li; Zinong Yang; Zhou Hong; Daping Xu; Zhihui Li; Shengjie Wang (PLoS ONE, 2025)
Agarwood is the resinous part of the injured tree of the Aquilaria species of the Thymelaeceae family, Qi-Nan is a type of agarwood that forms easily and benefits from a shortened inducing time, noted for features like its substantial resin, (2-phenylethyl) chromone and 2-[2-(4-methoxyphenyl) ethyl] chromone content. Although the content of agarotetrol in Qi-Nan is very low, it is still an important indicator for the agarwood quality. A validated method was developed to precisely quantify both agarotetrol and two aforementioned chromones, as well as ethanal extracts, within Qi-Nan to explore how the inducing time (half a year, one year, and two years) and different clones (YYZ, AS, RH, XGY) affect agarwood quality. Different clones and inducing time both have significant effects on agarwood quality. The agarwood quality of Qi-Nan does not necessarily improve with a longer inducing time. YYZ, AS, and RH clones reached to the best agarwood quality after two years of induction. The ethanol extracts content was among 46.82 ~ 48.59%, two chromones were among 10.57% ~ 14.05% after two years of induction. However, for XGY clone, the quality of agarwood after one year of induction was better than that after two years, which reached to the highest ethanol extracts (51.49%) and two chromones content reached to 12.43% and 12.91% after one year of induction. Therefore, for different clones of Qi-Nan, harvesting should be conducted at different time of induction for agarwood formations, which has theoretical implications for the cultivation and industrial development of cultivated Qi-Nan agarwood.